A dielectric composite and method for producing the same. - Ismail, Alyani; Abdan, Khalina; Mohamad, Nuraida; Mahdi, Mohd Adzir (2010)

(untitled)
The present invention relates to a dielectric composite for electronic component comprising a fiber mixed with a polymer coated with a conductive material characterized in that the fiber is a natural fiber and method for producing the same. The natural fiber is an attractive option due to their relatively cheapness, ability to recycle, low density, biodegradable and low environmental concerns. Compared to synthetic fiber made from glass, carbon and steel, natural fiber has a high aspect ratio and high strength to weight ratio. The composite with low dielectric constant is suited for use in printed circuit boards (PCB) for high frequency, high speed application and low power consumption of circuits in electronic component. This factor contributes to produce a high performance electronic component.